2018
DOI: 10.1038/s41598-018-35590-2
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the evolutionary history of F420-dependent dehydrogenases

Abstract: During the last decade the number of characterized F420-dependent enzymes has significantly increased. Many of these deazaflavoproteins share a TIM-barrel fold and are structurally related to FMN-dependent luciferases and monooxygenases. In this work, we traced the origin and evolutionary history of the F420-dependent enzymes within the luciferase-like superfamily. By a thorough phylogenetic analysis we inferred that the F420-dependent enzymes emerged from a FMN-dependent common ancestor. Furthermore, the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 48 publications
1
46
0
1
Order By: Relevance
“…In recent years, there has been increasing interest in F 420 -dependent enzymes for biocatalytic applications (5, 6, 35, 36). Therefore, the convenient production in E. coli along with the anticipation to discover novel enzymes and regeneration systems specialized for 3PG-F 420 opens intriguing prospects for biocatalysis and metabolic engineering.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in F 420 -dependent enzymes for biocatalytic applications (5, 6, 35, 36). Therefore, the convenient production in E. coli along with the anticipation to discover novel enzymes and regeneration systems specialized for 3PG-F 420 opens intriguing prospects for biocatalysis and metabolic engineering.…”
Section: Discussionmentioning
confidence: 99%
“…All structures solved to date from the LLHT family contain a non-prolyl cis peptide in β3 [23][24][25][26]. Recent phylogenetic reconstructions have shown that the F 420 -dependent LLHTs form two clades: the F 420 -dependent reductases and the F 420 -depented dehydrogenases [27]. The F 420 -reductases contain methylenetetrahydromethanopterin reductases (MERs), which catalyze the reversable, ring-opening cleavage of a carbon-nitrogen bond during the biosynthesis of folate in some archaea [28][29][30].…”
Section: The Llht Familymentioning
confidence: 99%
“…The first contains F 420 -dependent secondary alcohol dehydrogenases (ADFs) and the hydroxymycolic acid reductase from M. tuberculosis [31]. The second contains the F 420 -dependent glucose-6-phosphate dehydrogenases (FGDs) from Mycobacteria and Rhodococcus, while the third appear to be more general sugar-phosphate dehydrogenases [27]. In contrast to the heterodimeric structure of bacterial luciferase, the F 420 -dependent dehydrogenases form homodimers with the dimer interface burying a relatively large portion of the surface area of the monomers (≈2000 Å 2 , roughly 15% Catalysts 2019, 9, 868 5 of 18 of the total surface area) [24][25][26].…”
Section: The Llht Familymentioning
confidence: 99%
“…All structures solved to date from the LLHT family contain a non-prolyl cis peptide in β3 [23][24][25][26]. Recent phylogenetic reconstructions have shown that the F420-dependent LLHTs form two clades: the F420-dependent reductases and the F420-depented dehydrogenases [27]. The F420-reductases contain methylenetetrahydromethanopterin reductases (MERs), which catalyze the reversable, ring-opening cleavage of a carbon-nitrogen bond during the biosynthesis of folate in some archaea [28][29][30].…”
Section: The Llht Familymentioning
confidence: 99%
“…The first contains F420dependent secondary alcohol dehydrogenases (ADFs) and the hydroxymycolic acid reductase from M. tuberculosis [31]. The second contains the F420-dependent glucose-6-phosphate dehydrogenases (FGDs) from Mycobacteria and Rhodococcus, while the third appear to be more general sugar-phosphate dehydrogenases [27]. In contrast to the heterodimeric structure of bacterial luciferase the F420-dependent dehydrogenases form homodimers with the dimer interface burying a relatively large portion of the surface area of the monomers (≈ 2000 Å 2 , roughly 15% of the total surface area) [23,25,26].…”
Section: The Llht Familymentioning
confidence: 99%